2010
DOI: 10.1038/nm.2236
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody targeting of N-cadherin inhibits prostate cancer growth, metastasis and castration resistance

Abstract: The transition from androgen-dependent to castration-resistant prostate cancer (CRPC) is a lethal event of uncertain molecular etiology. Comparing gene expression in isogenic androgen-dependent and CRPC xenografts, we found a reproducible increase in N-cadherin expression, which was also elevated in primary and metastatic tumors of individuals with CRPC. Ectopic expression of N-cadherin in nonmetastatic, androgen-dependent prostate cancer models caused castration resistance, invasion and metastasis. Monoclonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
257
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 288 publications
(284 citation statements)
references
References 26 publications
23
257
1
3
Order By: Relevance
“…The present study showed that CRPC tumors in which AR expression was elevated showed mesenchymal characteristics manifested by increased expression of mesenchymal markers, suggesting that CRPC tumors may have highly invasive and metastatic potential. This is supported by a recent report showing that N-cadherin is up-regulated in CRPC tissues (Tanaka et al 2010). As shown in this study, AR expression was elevated in invasive prostate cancer, which is consistent with a previous report showing that higher levels of AR expression is correlated with extraprostatic extension, seminal vesicle invasion, and lymph-node involvement in radical prostatectomy specimens (Li et al 2004).…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed that CRPC tumors in which AR expression was elevated showed mesenchymal characteristics manifested by increased expression of mesenchymal markers, suggesting that CRPC tumors may have highly invasive and metastatic potential. This is supported by a recent report showing that N-cadherin is up-regulated in CRPC tissues (Tanaka et al 2010). As shown in this study, AR expression was elevated in invasive prostate cancer, which is consistent with a previous report showing that higher levels of AR expression is correlated with extraprostatic extension, seminal vesicle invasion, and lymph-node involvement in radical prostatectomy specimens (Li et al 2004).…”
Section: Discussionsupporting
confidence: 93%
“…S7). Our results demonstrate that tumors driven by NICD1 in combination with kRas G12D , myrAKT, and Myc exhibit EMT features, a phenotype that may characterize invasive, poorly differentiated carcinoma (42)(43)(44)(45).…”
Section: Gene-expression Profiling Of Tumors Driven By Nicd1 In Combimentioning
confidence: 66%
“…7e9 Hallmarks of EMT in PC include disruption of adherens junctions through down-regulation of E-cadherin, 2 concomitant with a development of a migratory phenotype and up-regulation of mesenchymal markers, such as N-cadherin, vimentin, and fibronectin. 10,11 Loss of E-cadherin results from mutations, DNA methylation, or silencing of E-cadherin promoter regions during transcription. 12,13 A predominant repressor of E-cadherin gene transcription and an inducer of N-cadherin expression during EMT is Twist1, 14e16 which belongs to the group of EMT transcription factors (Slug, Snail, Zeb1, and Zeb2).…”
mentioning
confidence: 99%